Doctor-Patient Relationship in the Eyes of Medical Professionals in China During the COVID-19 Pandemic: A Cross-Sectional Study - Zhou, Yanan; Yang, Winson Fu Zun; Ma, Yuejiao; Wu, Qiuxia; Yang, Dong; Liu, Tieqiao; Wu, Xiaoming (Frontiers in Psychiatry, 2021)
Background: Doctor-patient relationship (DPR) is very important for patient out-comes, especially during a public health emergency like the COVID-19 pandemic. However, few studies have evaluated DPR and related sentiments from medical professionals’ perspectives. Thus, the aim of the study is to provide a better understanding of DPR from medical professionals’ perspectives during the COVID-19 pandemic in China. Methods: A total of 979 medical professionals, including doctors, nurses, technicians, and other workers have completed a series of questionnaires to evaluate their attitudes toward DPR, trust, violence against doctors, factors that affected and improved DPR, and the importance of these factors on DPR. Analyses of variances (ANOVA) and linear regressions were used to analyze the effects of the pandemic, demographic variables, and various elements on DPR. Results: One-way ANOVA revealed a significant effect of education on recent DPR (F(2, 976)=6.17, p<0.001 and trust at F(2, 976)=9.54, p<0.001), indicating that individuals with higher level of education (bachelor’s degree, Master’s degree and above) showed poorer recent DPR and lower level of trust. The level of hospital also showed a significant effect on trust (F(5, 973)=3.79, p=0.0021). Cochran’s Q test revealed a significant difference in factors that affected (Q(11)=3,997.83, p<0.001) and improved (Q(8)=3,304.53, p<0.001) DPR. Backward stepwise linear regressions revealed predictors for changes during (F(9, 969)=21.17, p<0.001, R2=0.16), shortly after (F(7, 971)=54.98, p<0.001, R2=0.28), and long after (F(10, 968) =37.83, p<0.001, R2=0.29) the pandemic. Conclusions: Medical professionals’ perceptions of DPR is important as they provide basis for the improvement in working environment of medical professionals and hospital visiting experience of patients, as well as healthcare policy making and preparation for future public health emergencies.